Shear behaviour and calculation model for stud-UHPC connections: Finite element and theoretical analyses. (1st March 2022) - Xu, Qizhi; Sebastian, Wendel; Lu, Kaiwei; Yao, Yiming; Wang, Jingquan
Highlights: A three-dimensional nonlinear finite element model was established and validated by the experimental results of the push-out tests. The parametric analyses were conducted to discuss the influences of the stud diameter, concrete strength, stud aspect ratio and cover thickness on the shear behavior for stud-UHPC connections. An algebraic model characterized by elastic, elasto-plastic and plastic stages is proposed to predict the load-slip relationships, which agrees well with the experimental curves. Abstract: This paper focuses on prediction of longitudinal shear behaviour including load-slip relationships of stud connections between UHPC (ultra-high performance concrete) slabs and steel beams. An experimentally validated finite element (FE) model is used for parametric studies to understand the influences of stud diameter, concrete strength, stud aspect ratio and cover thickness on the shear behaviour. This study shows that the shear strength increases as parabolic and linear functions of the stud diameter and concrete strength, respectively, especially for large diameter studs embedded in higher strength concretes. Smaller stud aspect ratios and cover thicknesses are important to ensure stud fracture, thereby leading to an optimal UHPC slab thickness. Moreoever, an algebraic calculation model characterized by elastic, elasto-plastic and plastic stages is proposed, in which the key parameters, including the yielding slip of concrete, the effective plastic length in the concrete and the slip at onset of stud yielding are defined based on the FE results. This algebraic model's predictions are successfully compared with the experimental curves from different published studies.